Inspired by Malaysian batik / Muhammad Shafiq Mahadi - Mahadi, Muhammad Shafiq (2022)
Bulky Hinges Bracelet inspired by Malaysian Batik motif. Malaysian Batik is the traditional outfit of the local community in Malaysia. The wearing of the sheath is believed to have been on this earth since 15th century. The ﬂower motif on Malaysian Batik have used for this product for present the beauty of the ﬂower motif on Malaysian Batik.